Inclusion of interleukin-6 improved the performance of postoperative acute lung injury prediction for patients undergoing surgery for thoracic aortic disease - Li, Huili; Feng, Weiqi; Wang, Qiuji; Li, Chenxi; Zhu, Jiade; Sun, Tucheng; Wu, Jinlin (Frontiers in Cardiovascular Medicine, 2023)
Background We studied acute lung injury (ALI) in thoracic aortic disease (TAD) patients and investigated the predictive effect of interleukin-6 (IL-6) in acute lung injury after thoracic aortic disease. Methods Data on 188 TAD patients, who underwent surgery between January 2016 to December 2021 at our hospital, were enrolled in. We analyzed acute lung injury using two patient groups. Patients with No-ALI were 65 and those with ALI were 123. Univariate logistic, LASSO binary logistic regression model and multivariable logistic regression analysis were performed for acute lung injury. Results Preoperative IL-6 level was lower (15.80[3.10,43.30] vs. 47.70[21.40,91.60] pg/ml, p < 0.001) in No-ALI group than in ALI group. The cut-off points, determined by the ROC curve, were preoperative IL-6 > 18 pg/ml (area under the curve: AUC = 0.727). Univariate logistic regression analysis showed 19 features for TAD appeared to be early postoperative risk factors of acute lung injury. Using LASSO binary logistic regression, 19 features were reduced to 9 potential predictors (i.e., Scrpost + PLTpost + CPB > 182 min + D-dimerpost + D-dimerpre + Hypertension + Age > 58 years + IL6 > 18 pg/ml + IL6). Multivariable logistic regression analysis showed that Postoperative creatinine, CPB > 182 min and IL-6 > 18 pg/ml were early postoperative risk factors for ALI after TAD, and the odds ratios (ORs) of postoperative creatinine, CPB > 182 min and IL-6 > 18 pg/ml were 1.006 (1.002–1.01), 4.717 (1.306–19.294) and 2.96 (1.184–7.497), respectively. When postoperative creatinine, CPB > 182 min and IL-6 > 18 pg/ml (AUC = 0.819), the 95% confidence interval [CI] was 0.741 to 0.898. Correction curves were nearly diagonal, suggesting that the nomogram fit well. The DCA curve was then drawn to demonstrate clinical applicability. The DCA curve showed that the threshold probability of a patient is in the range of 30% to 90%. Conclusions The inclusion of interleukin-6 demonstrated good performance in predicting ALI after TAD surgery.